Self-pollination and its implication in invasiveness of Helianthus annuus ssp. annuus and H. petiolaris - Gutierrez, Agustina (2014)
Helianthus petiolaris and H. annuus are exotic invaders that have spread widely in central Argentina in the last 70 years. As other annuals of the same genus, these species are outcrossers bearing a sporophytic self-incompatible mechanism. We investigated the ability to self-pollinate in plants of five accessions of each species, its influence on some reproductive traits, and compared to the cultivated sunflower, in which breeding for self-compatibility has been very successful. Plants were allowed to self-pollinate in bagged heads, manually forced to self-pollinate or allowed to cross-pollinate. Although both invasive species were confirmed as self-incompatible, some plants within most accessions were able to self-pollinate. There was no significant interaction between accessions and pollination type for most traits, except for seed set which was attributed to interspecific introgression. The self-compatibility of some plants was transmitted to their progeny. No significant correlation between self-pollination and spread distance from the proposed entry point for the exotic species was found. The occurrence of self-compatible plants was demonstrated in both species and this fact could in part explain the high invasive ability of annual Helianthus species in Argentina.